Uzbekistan's Integration into the International Financial System and its Role in Developing Entrepreneurship - kizi, Mamayusupova Shokhina Ulugbek (Journal of Economics, Bussiness and Management Issues, 2024)
This article discusses the activities of international integration associations, the necessity of developing trade relations with the countries included in these associations, as well as the importance of enhancing cooperative relationships with international financial organizations. The article highlights the increasing connection of our independent republic with major global financial institutions and international Islamic financial funds. Consequently, this development enables Uzbek entrepreneurs to access the global market, produce goods that meet international standards, and ultimately contributes to the economic and social prosperity of the republic. It also explains how small and medium-sized enterprises in Uzbekistan can achieve significant success.